Rancang Bangun Purwarupa Alat Penyortir Kualitas Telur Ayam Berbasis Arduino Uno - Rafly Hadi Pangestu; Ch, Syafaruddin; Supriono (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
The demand for animal products, especially eggs, as a source of easily digestible and high-quality protein, continues to increase significantly. Eggs play an important role in nutrition due to their rich protein content. However, eggs have weaknesses in terms of durability, as they can deteriorate due to various factors such as natural damage, chemical exposure, and microbial contamination that can enter through their shells. Therefore, sorting eggs is crucial to ensure their quality before consumption. Traditional sorting methods commonly used involve using a flashlight in dark rooms or employing water immersion techniques, which have limitations in accuracy and efficiency. In light of these issues, this research aims to develop an egg sorting device using Arduino Uno as the microcontroller, along with a Light Dependent Resistor (LDR) for detecting the condition of the eggs and a Load Cell for measuring the weight of the eggs as the basis for sorting. The results of this study indicate that the combination of these two sensors can minimize errors in the sorting process and expedite egg production activities. Consequently, this device is expected to provide solutions for poultry farmers and egg sellers in enhancing product quality and increasing consumer satisfaction.